Red-Shifted Aequorin-Based Bioluminescent Reporters for in Vivo Imaging of Ca Signaling - Thomas Curie; Kelly L. Rogers; Cesare Colasante; Philippe BrûClet (Molecular Imaging)
Real-time visualization of calcium (Ca 2+ ) dynamics in the whole animal will enable important advances in understanding the complexities of cellular function. The genetically encoded bioluminescent Ca 2+ reporter green fluorescent protein–aequorin (GA) allows noninvasive detection of intracellular Ca 2+ signaling in freely moving mice. However, the emission spectrum of GA is not optimal for detection of activity from deep tissues in the whole animal. To overcome this limitation, two new reporter genes were constructed by fusing the yellow fluorescent protein (Venus) and the monomeric red fluorescent protein (mRFP1) to aequorin. Transfer of aequorin chemiluminescence energy to Venus (VA) is highly efficient and produces a 58 nm red shift in the peak emission spectrum of aequorin. This substantially improves photon transmission through tissue, such as the skin and thoracic cage. Although the Ca 2+ -induced bioluminescence spectrum of mRFP1-aequorin (RA) is similar to that of aequorin, there is also a small peak above 600 nm corresponding to the peak emission of mRFP1. Small amounts of energy transfer between aequorin and mRFP1 yield an emission spectrum with the highest percentage of total light above 600 nm compared with GA and VA. Accordingly, RA is also detected with higher sensitivity from brain areas. VA and RA will therefore improve optical access to Ca 2+ signaling events in deeper tissues, such as the heart and brain, and offer insight for engineering new hybrid molecules.